A Single-Crystal Open-Capsule Metal–Organic Framework - Wei, Yong-Sheng; Zhang, Mei; Kitta, Mitsunori; Liu, Zheng; Horike, Satoshi; Xu, Qiang (Journal of the American Chemical Society, 2019)
Micro-/nanocapsules have received substantial attention due to various potential applications for storage, catalysis, and drug delivery. However, their conventional enclosed non-/polycrystalline walls pose huge obstacles for rapid loading and mass diffusion. Here, we present a new single-crystal capsular-MOF with openings on the wall, which is carefully designed at the molecular level and constructed from a crystal-structure transformation. This rare open-capsule MOF can easily load the largest amounts of sulfur and iodine among known MOFs. In addition, derived from capsular-MOF and melamine through pyrolysis–phosphidation, we fabricated a nitrogen-doped capsular carbon-based framework with iron–nickel phosphide nanoparticles immobilized on capsular carbons interconnected by plentiful carbon nanotubes. Benefiting from synergistic effects between the carbon framework and highly surface-exposed phosphide sites, the material exhibits efficient multifunctional electrocatalysis for oxygen evolution, hydrogen evolution, and oxygen reduction, achieving well-qualified assemblies of an overall water splitting (low potential of 1.59 V at 10 mA·cm–2) and a rechargeable Zn–air battery (high peak power density of 250 mW·cm–2 and excellent stability for 500 h), which afford remarkably practical prospects over previously known electrocatalysts.